Arabic Language Learning Strategy And The Problems Of Its Application At LKP Ibnu Khaldun Driyorejo Gresik - Sholihudin Al Ayubi (JOSSE: Journal of Social Science and Economics, 2022)
This article is the result of research that describes Arabic learning strategies and the problems faced by teachers. LKP Ibn Khaldun is an Arabic language development institution that uses multigames based on the